Identifying the perfusion deficit in acute stroke with resting‐state functional magnetic resonance imaging. Issue 1 (1st February 2013) - Lv, Yating; Margulies, Daniel S.; Cameron Craddock, R.; Long, Xiangyu; Winter, Benjamin; Gierhake, Daniel; Endres, Matthias; Villringer, Kersten; Fiebach, Jochen; Villringer, Arno
Abstract: Temporal delay in blood oxygenation level–dependent (BOLD) signals may be sensitive to perfusion deficits in acute stroke. Resting‐state functional magnetic resonance imaging (rsfMRI) was added to a standard stroke MRI protocol. We calculated the time delay between the BOLD signal at each voxel and the whole‐brain signal using time‐lagged correlation and compared the results to mean transit time derived using bolus tracking. In all 11 patients, areas exhibiting significant delay in BOLD signal corresponded to areas of hypoperfusion identified by contrast‐based perfusion MRI. Time delay analysis of rsfMRI provides information comparable to that of conventional perfusion MRI without the need for contrast agents. ANN NEUROL 2013.